Infective endocarditis in renal transplant recipients: one centers experience - Pereira,L (2018)
Background: Infective endocarditis (IE) is rarely described among renal transplant recipients. Methods: We conducted a retrospective study to identify all cases of IE in our renal transplant unit between 1992 and 2012 to elucidate IEs clinical features and outcomes. Modified Duke criteria were applied to confirm diagnosis and patient evolution was evaluated. Results: Between 1992 and 2012, our renal transplant unit performed 1065 renal transplants. Seven episodes of IE were identified in six patients. Median age at presentation was 59 years and most cases occurred in males (71.4%). Blood cultures were negative in 42.9% of patients. Gram positive coccus were the most frequent etiologic agents. There were no fungal endocarditis. Aortic valve was involved in all patients. Three patients underwent cardiac surgery. Mortality at 30 days and 2 years were 16.7%. Conclusion: Infective endocarditis in renal transplant patients remains a rare disease. The diagnosis is challenging considering nonspecific presentation and the high proportion of negative blood cultures.